Sistem Pakar Diagnosis Penyakit Pernafasan Pada Manusia dengan Metode Forward Chaining - Mhd Furqan; Abdul Halim Hasugian; Tria Elisa (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Respiratory disease is an infectious disorder that often occurs compared to other diseases. Due to the lack of handling and people who take it lightly with the symptoms caused by respiratory diseases in humans, causing the disease to get worse. The purpose and intent of this research is to facilitate and help the public to diagnose respiratory diseases efficiently and effectively. Seeing the problem occurs, a web-based application is made to overcome it. This expert system has analyzed data consisting of 6 diseases, namely tuberculosis, bronchitis, pneumonia, pleurisy, tonsillitis, and asthma. So that there are 40 disease symptom data that form a symptom rule and form the right diagnosis results. This web-based expert system for diagnosing respiratory diseases in humans is used with the forward chaining method. So the result of this research is an application or web-based expert system for diagnosing respiratory diseases in humans.